Rapid commercial conversion of agriculture land in Lahore Division, Pakistan - Imtiaz Hassan (Advancements in Life Sciences, 2018)
Background: Pakistan is experiencing rapid population growth and urbanization which require land in urban areas. Rapid commercial conversion of has dramatically changed agriculture land base. The present conversion policy is not capable to achieve principles and objectives of sustainability especially in agriculture areas.